(untitled) (Journal of Economic Research & Business Administration, 2017)
This article discusses the functioning of the land tax in the tax system of the Republic of Kazakhstan. The mechanism of functioning of the land tax. The analysis of the role of land tax in the tax revenues of the state budget for 2013-2015 GG Land tax is a direct tax, they are directed to the object of taxation, property taxes are taxen- are difficult to hide from the tax. Land tax applies to fixed taxes, and enter fully into the local budget revenues. The article deals with some problems in the functioning of the land. Comprehensive study of theoretical aspects of functioning of tax on property and approaches to its construction in the world can help to optimize operating in Kazakhstan, property tax and land tax. Therefore, the research methods and techniques of land valuation and determination of the tax base in this area is quite relevant.